Resolving Arrears Maintaince for Children: Penang Case Study Year 2018 - Ismail, Mohd Hazwan; Sulong, Jasni (European Publisher, 2019)
In Islam, it is an obligation of a father to pay maintenance to his children during marriage and after divorce, even though the custody of his kids was given to ex-wife. Therefore, if a father fails to perform his duty, the arrears maintenance will be considered as a debt. This opinion was based on allegation that a default to pay maintenance will lead children and ex-wives facing financial difficulties in their current and future life. They need support for foods, clothes, shelter, education as well as medical treatment. Therefore, the compulsory payment that was ratified by the shariah court must be counted as an outstanding sum. In this case, various steps have been taken by the Shariah law in order to ensure financial support is constantly paid to the children. Therefore, the purpose of this study is to investigate the strategy taken by the shariah court in responding towards arrear maintenance of a father. The findings will portray statistic of cases, as well as the cost of arrear maintenance that involved. It was found that in Penang, the establishment of the Department of Family Support under the shariah court was greatly helps mothers in obtaining this deferred maintenance. Through enforcement of the judgemental debt summon or judgment notice by the shariah court, most of the default father paid the total amount that they have owed towards their children.